Implementation of the Direct Reading Method Assisted by Digital Media to Improve English Vocabulary Mastery: Penerapan Metode Membaca Langsung Berbantuan Media Digital dalam Meningkatkan Penguasaan Kosakata Bahasa Inggris - Muhria, Lanlan; Kholidah, Endang Siti Nur; Solihin, Rully Khoeru (Journal of Society and Development, 2024)
Vocabulary mastery is a fundamental component of English learning that underpins students’ ability to read, write, speak, and listen effectively. However, many Indonesian learners still rely on passive memorization and translation strategies, which are less effective for long-term vocabulary retention and communicative competence. This study investigates the application of the Direct Reading Method assisted by digital media as an innovative strategy to improve students’ English vocabulary mastery. The integration of digital resources, such as interactive e-books, vocabulary applications, and multimodal content, aims to create a more contextual, engaging, and effective learning environment that meets the needs of the digital generation. This research employed a quasi-experimental design with a pretest-posttest control group. Participants were high school students selected purposively based on low initial vocabulary scores and access to digital devices. Data were collected using vocabulary tests, observation sheets, and motivation questionnaires. Quantitative data were analyzed through t-tests, while qualitative findings were drawn from observations and student responses. The findings demonstrate that the experimental group, taught using the Direct Reading Method with digital media, showed significantly greater improvement in vocabulary mastery than the control group taught with conventional methods. The experimental group’s average score increased by +23.4 compared to +11.3 in the control group, with statistical tests confirming significant differences (p < 0.01). Furthermore, students in the experimental group exhibited higher engagement (82%), stronger motivation, and a greater desire to continue using the method. In conclusion, combining Direct Reading with digital media not only enhances vocabulary mastery but also fosters active participation and learning motivation. This approach offers an effective, interactive, and technology-integrated model of vocabulary learning suitable for 21st-century education.